2003
DOI: 10.1093/brain/awg165
|View full text |Cite
|
Sign up to set email alerts
|

Cortical correlates of vestibulo-ocular reflex modulation: a PET study

Abstract: To elucidate cortical correlates of vestibulo-ocular reflex (VOR) modulation, we observed cortical activation during fixation suppression and habituation of caloric vestibular nystagmus in 12 normal subjects, using PET. Significant positive correlation between regional cerebral blood flow (rCBF) and slow phase eye velocity of caloric nystagmus was observed in the middle and posterior insula, inferior parietal lobule, temporal pole, right fusiform gyrus, lingual gyrus, and cerebellar vermis and hemisphere. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
58
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(66 citation statements)
references
References 90 publications
(97 reference statements)
8
58
0
Order By: Relevance
“…Congruently, epileptic patients with vestibular aurae suffer from lesions surrounding the superior temporal gyrus and the temporoparietal cortex [99,107]. This location has also been confirmed by functional neuroimaging studies in healthy subjects using caloric and galvanic stimulation of the peripheral vestibular system revealing unanimously predominant activations centered on the TPJ and insula [6,19,20,32,39,46,47,50,51,70,72,85,94,95,110,112,118] with activations in the superior temporal gyrus, posterior insula, inferior parietal lobule (angular and supramarginal gyri), and postcentral gyrus. Although many regions surrounding the TPJ/insula have been found activated, opinions concerning the exact location of the human homologue of the PIVC differ (Fig.…”
Section: The Vestibular Cortexmentioning
confidence: 80%
“…Congruently, epileptic patients with vestibular aurae suffer from lesions surrounding the superior temporal gyrus and the temporoparietal cortex [99,107]. This location has also been confirmed by functional neuroimaging studies in healthy subjects using caloric and galvanic stimulation of the peripheral vestibular system revealing unanimously predominant activations centered on the TPJ and insula [6,19,20,32,39,46,47,50,51,70,72,85,94,95,110,112,118] with activations in the superior temporal gyrus, posterior insula, inferior parietal lobule (angular and supramarginal gyri), and postcentral gyrus. Although many regions surrounding the TPJ/insula have been found activated, opinions concerning the exact location of the human homologue of the PIVC differ (Fig.…”
Section: The Vestibular Cortexmentioning
confidence: 80%
“…Finally, on a methodological point of view, we note that, even though most neuroimaging studies have been conducted with participants placed in darkness and with eyes closed, one can wonder what was the influence of the retinal image slip induced by caloric or galvanic stimulation in studies that used free vision. Indeed, the velocity of the caloric nystagmus was found to correlate with the brain activity in several regions overlapping with the vestibular cortex, including the insula, inferior parietal lobule, fusiform and lingual gyrus, and the cerebellum (Naito et al, 2003). These authors also demonstrated that visual fixation was related to a deactivation of the vestibular cortex.…”
Section: Vestibular Projections To Striate and Extrastriate Visual Comentioning
confidence: 89%
“…Functional neuroimaging studies performed in healthy subjects during caloric and galvanic vestibular stimulation have unanimously demonstrated activation of the posterior insula and temporo-parietal junction (TPJ), that could represent the human homologue of the monkey PIVC (Bense et al, 2001;Bottini et al, 1994Bottini et al, , 1995Bottini et al, , 2001Bucher et al, 1998;Dieterich et al, 2003;Eickhoff et al, 2006b;Emri et al, 2003;Fasold et al, 2002;Fink et al, 2003;Friberg et al, 1985;Hegemann et al, 2003;Indovina et al, 2005;Lobel et al, 1998;Marcelli et al, 2009;Miyamoto et al, 2007;Naito et al, 2003;Petit and Beauchamp, 2003;Schlindwein et al, 2008;Stephan et al, 2005;Suzuki et al, 2001;Tuohimaa et al, 1983;Vitte et al, 1996). These activations centered on the superior temporal gyrus, the posterior and anterior insula, or the inferior parietal lobule (Fig.…”
Section: Vestibular Projections To the "Parieto-insular Vestibular Comentioning
confidence: 99%
“…At 5°C as final temperature for cold we decreased the probability of eliciting ice-water nystagmus (Batuecas-Caletrio et al 2009). Temperatures used in our experiments were also applied in previous studies involving caloric stimulation (e.g., Fasold et al 2002;Naito et al 2003;Suzuki et al 2001).…”
Section: Methodsmentioning
confidence: 99%
“…However, by applying temperatures only through pods and primarily to sites of the ear canal in close vicinity to the pods we reduced the stimulation intensity compared with procedures involving immediate contact of hot or cold medium to the skin surface of the entire ear canal; this is the case for direct injection of water (DeutschlĂ€nder et al 2002;Dieterich et al 2003;Suzuki et al 2001), tempered air (Naito et al 2003), or nitrogen gas (Fasold et al 2002). Therefore, to increase the likelihood of inducing self-motion sensations with only mild vestibular stimulation, we decided to use bilateral caloric stimulation in our experiments.…”
Section: Methodsmentioning
confidence: 99%